2019
DOI: 10.1001/jamapsychiatry.2018.4166
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polygenic Liabilities for Major Depression, Bipolar Disorder, and Schizophrenia With Risk for Depression in the Danish Population

Abstract: ; for the Bipolar Disorder Working Group of the Psychiatric Genomics Consortium IMPORTANCE Although the usefulness of polygenic risk scores as a measure of genetic liability for major depression (MD) has been established, their association with depression in the general population remains relatively unexplored. OBJECTIVE To evaluate whether polygenic risk scores for MD, bipolar disorder (BD), and schizophrenia (SZ) are associated with depression in the general population and explore whether these polygenic lia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 54 publications
8
72
0
2
Order By: Relevance
“…and BD2018 predicted the risk of MDD in children and adults (Musliner et al, 2019), though the PRS for BD2018 predicted the…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…and BD2018 predicted the risk of MDD in children and adults (Musliner et al, 2019), though the PRS for BD2018 predicted the…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have investigated the polygenic prediction of MDD (Halldorsdottir et al, 2019;Musliner et al, 2019) and BD and SCZ (Musliner et al, 2019) using PRSs calculated using the same GWAS summary statistics as we did (Ripke et al, 2014;Ruderfer et al, 2018;Wray et al, 2018). While these studies were conducted outside the perinatal period, they are relevant due to the partially shared genetic component among the different disorders (Cross-Disorder Group of the Psychiatric Genomics et al, 2013;Lee et al, 2019;Viktorin et al, 2016), risk factors and biological mechanisms of vulnerability (Roy & Campbell, 2013;Schiller et al, 2015;Serati, Redaelli, Buoli, & Altamura, 2016;Yim et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Adding to emerging psychiatric research integrating genetic and EHR data (Musliner et al, 2019), we found that polygenic risk for depression was prospectively associated with depression outcomes in a healthcare system, such that individuals with the highest polygenic loading for depression showed over 50% higher odds of incident depression in a two-year window than those at low polygenic risk. This association persisted even when accounting for EHR evidence of prior depression, suggesting that polygenic risk scores have potential not only to explain lifetime depression but also the likelihood of incident episodes-though remains to be further tested.…”
Section: Discussionmentioning
confidence: 95%
“…The most recent molecular genetic study of youth depression was based on the Danish iPsych cohort that utilized health record registry data and included those with a clinic recorded diagnosis of depression from age 10 years onwards [34]. These investigators also observed somewhat higher schizophrenia PRS in earlier-onset depression (those aged 10 to 15 years) with MDD PRS showing strongest associations for depression with age-at-onset between 16 and 25 years.…”
Section: Depression: Same Disorder At Different Ages?mentioning
confidence: 99%